2018
DOI: 10.2147/jpr.s181079
|View full text |Cite
|
Sign up to set email alerts
|

Multiple effectiveness aspects of tapentadol for moderate–severe cancer-pain treatment: an observational prospective study

Abstract: BackgroundPrevious studies have shown the efficacy of tapentadol (TP) for chronic cancer pain. We evaluated multiple effectiveness aspects of TP prolonged release on moderate–severe cancer-related pain, neuropathic pain (NeP), patient satisfaction, and quality of life.MethodsAn observational prospective study was conducted on 80 cancer patients. Opioid-naïve patients received a starting dose of prolonged-release TP 50 mg twice daily, and opioid-experienced patients were switched to TP, not to exceed 500 mg/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…All patients with nociceptive pain and more than 90% of patients with neuropathic pain or mixed pain were responders. These findings highlight tapentadol’s effectiveness not only for cancer-related nociceptive pain, but also neuropathic pain and the results are mirrored in other studies [ 21 , 24 , 30 32 ].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…All patients with nociceptive pain and more than 90% of patients with neuropathic pain or mixed pain were responders. These findings highlight tapentadol’s effectiveness not only for cancer-related nociceptive pain, but also neuropathic pain and the results are mirrored in other studies [ 21 , 24 , 30 32 ].…”
Section: Discussionsupporting
confidence: 77%
“…We acknowledge that we are unable to draw conclusive statements regarding tapentadol's safety as opioid-induced adverse effects extend beyond nausea and vomiting. Nevertheless, published literature have demonstrated the acceptable safety and tolerability profile of tapentadol in patients with cancer-related pain [21,24,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Cascella et al28 have recently published the results of an observational prospective study in 80 cancer patients, either opioid-naive or pretreated. In total, 70 out of 80 patients (88%) were responders.…”
Section: Clinical Evidence For Tapentadol In the Treatment Of Mixed Pmentioning
confidence: 99%
“…A clinical report indicated that in a patient with PD it induced bradykinesia and rigidity postoperatively after deep brain stimulation 49. Tapentadol is a molecule characterized by a dual mechanism by acting on the MORs and through inhibition of the reuptake of noradrenaline, thereby, increasing endogenous modulating activity 50. Despite its potential efficacy, there are no data on PRP.…”
Section: Pharmacological Considerationsmentioning
confidence: 99%